Pengaruh Keterlibatan Orang Tua dalam Pengelolaan Waktu Belajar Siswa di Rumah terhadap Prestasi Akademis di Sekolah Dasar - Taofik Hidayat, Ade; Kurniawati, Cucu (Papanda Publisher, 2023)
This study aims to explore the influence of parental involvement in managing students' study time at home on their academic performance in Cingambul I Elementary School (SDN). Through a quantitative approach, data were collected using questionnaires distributed to parents or guardians and students' report card records. Data analysis indicated a significant relationship between the level of parental involvement and students' academic performance. Parents who were more involved tended to have children with higher academic achievement. The implications of this study include the need to develop learning strategies that actively involve parents, support parents in increasing their involvement, and the crucial role of policymakers in creating an inclusive and responsive educational environment. By strengthening collaboration between schools and families, it is hoped that a better learning environment can be created, motivating students and enhancing their academic performance. This conclusion makes a significant contribution to strengthening elementary education, with the hope that every child will have an equal opportunity to achieve academic success.